FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Morika Wijaya; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to examine factors including profitability, leverage,company size, sales growth and liquidity on company value in manufacturingcompanies listed on the Indonesia Stock Exchange in 2017-2019. This study wasconducted using a purposive sampling method with valid data for 32 samples ofmanufacturing companies listed on the Indonesia Stock Exchange. Data analysis wasperformed using descriptive statistics and regression hypothesis testing using Eviewssoftware version 10. The results of this study indicate that leverage has a positive effect on firm value. Profitability, company size, sales growth, and liquidity have no effect on firm value. The implication of this research is the need for more attention toprofitability, leverage, company size, sales growth and liquidity which are factors thatcan increase firm value